Nonlinear behavior in high-intensity discharge lamps. (19th May 2016) - Baumann, Bernd; Schwieger, Joerg; Wolff, Marcus; Manders, Freddy; Suijker, Jos
Abstract: The light flicker problem of high intensity discharge lamps is studied numerically and experimentally. It is shown that in some respects the systems behave very similar to the forced Duffing oscillator with a softening spring. In particular, the jump phenomenon and hysteresis are observed in the simulations and in the experiments.